PENGARUH HUMAN RELATION DAN LINGKUNGAN KERJA TERHADAP KINERJA KARYAWAN PADA PTT. MILLENIUM PHARMACON INTERNATIONAL, TBK CABANG BANJARMASIN - Eny Siswi Amiarti; Hairudinor; Sugiharto; Irwansyah (Business Administration, FISIP ULM, 2023)
The purpose of this study is to ascertain and evaluate the relative and concurrent effects of workplace culture and human relations on workers' performance at the Banjarmasin branch of PT. Millennium Pharmachon International Tbk. A quantitative research approach is being used. Saturated sampling techniques were used to select 32 respondents for the sample. A questionnaire was used for data collection, and the SPSS 26 software was used for multiple linear regression analysis of the data. The findings of the study indicate that while the work environment has a significant impact on employee performance, human relations has a negligible effect. The aspects of the workplace and interpersonal relationships both have a big impact on how well employees perform.